MOTIVASI MAHASISWA MEMILIH JURUSAN PENDIDIKAN LUAR BIASA DI PERGURUAN TINGGI - Syafrimen Syafril (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
Choosing a career as a special education teacher (PLB) has many challenges as well as fun, not everyone is interested in this profession if not motivated by strong motivation. This study aims to find out the students motivation to choose special education teacher major (PLB) in college. This study used qualitative method with case study design approach. The data source was taken from seventeen informants through in-depth interviews selected using purposive sampling techniques; all informants are active students who chose special education teacher major (PLB) at Padang State University in 2017, 2018 and 2019. All interview results are then analyzed thematically using NVivo 10 qualitative analysis software. The results of the analysis showed that there were seven motivations of students to choose special education teacher major. The seven motivations are: i) having relatives with special need, (ii) the limited amount of special education teacher at school, (iii) the desire to become special education teacher, iv) the encouragement of parents, v) higher job opportunities after graduation, vi) teachers are noble professions, vii) love the world of children with special need. The results of this study can be used as preliminary data for subsequent researchers in examining these issues in different contexts and issues